Churn-annular gas-liquid flows in large diameter vertical pipes - Van der Meulen, Gerrit Pieter (2012)
This thesis presents an investigation on the churn to annular flow pattern boundary in an 11 m tall, 127 mm id vertical riser. Experimental data on film thickness, pressure drop and drop size and velocity was analysed and interpreted. Entrained fraction, interfacial and wall shear stresses and the interfacial friction were calculated from the experimental data.